2005
DOI: 10.1093/jjco/hyi077
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Paclitaxel and Carboplatin in Advanced Gastric Cancer Previously Treated with 5-Fluorouracil and Platinum

Abstract: Combination chemotherapy with paclitaxel and carboplatin is feasible in patients with advanced gastric cancer who were previously treated with 5-fluorouracil and platinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…There were several possible explanations for improved treatment outcome over these periods. The proportion of patients who received sequential second-or third-line chemotherapy increased [36][37][38]. Although the role of salvage chemotherapy was not proven in advanced gastric cancer until the late 2000s, two recent phase III trials demonstrated the benefit of the second-line chemotherapy for the improvement of survival outcome in patients with advanced gastric cancer [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…There were several possible explanations for improved treatment outcome over these periods. The proportion of patients who received sequential second-or third-line chemotherapy increased [36][37][38]. Although the role of salvage chemotherapy was not proven in advanced gastric cancer until the late 2000s, two recent phase III trials demonstrated the benefit of the second-line chemotherapy for the improvement of survival outcome in patients with advanced gastric cancer [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…This synergy has led to the development of paclitaxelplatinum combination regimens in a number of solid tumors, including gastric cancer. Various phase II studies of 3-weekly paclitaxel-containing combinations in the treatment of patients with advanced gastric cancer are listed in Table 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Combination regimens of paclitaxel plus platinum, or paclitaxel plus 5-FU, or both, yielded response rates of 32%-65% and MSTs of approximately 11 months (range, 6-14 months) in a fi rst-line treatment setting.…”
Section: Administration Of Paclitaxel Every 3 Weeks (3-weekly)mentioning
confidence: 99%
“…Paclitaxel (PTX; Figure 1) is a taxane that is derived from the bark of the Pacific yew tree Taxus brevifolia and was first shown to have anti-tumor activity in 1971 by Wani et al PTX may be used alone or in combination with other chemotherapy agents to treat many different types of cancer, including leukemia, lymphoma, and cancers of the head, neck, breast, esophagus, stomach, bladder, prostate, endometrium (uterus), and cervix (Wani et al, 1971;Rowinsky, 1993;Roth, 1995;McGuire et al, 1996;Seidman et al, 1996;Younes et al, 1997;Fountzilas et al, 1999;Kelly et al, 2001;Markman and Fowler, 2004;Chang et al, 2005;Ilson et al, 2007;Ward et al, 2007). The principal mechanism of its anti-cancer effect is to disrupt microtubule stability, thereby preventing cell growth (Schiff et al, 1979;Horwitz, 1980, 1981;Baum et al, 1981).…”
Section: Introductionmentioning
confidence: 99%